(untitled) (Scientific journal of the Fergana State University, 2025)
This article analyzes dialogic speech, its structural units and the concepts of speech act. The article also studies the phenomenon of intentional analysis, which expresses the communicative purpose of the speaker, based on examples. In addition, the role of locutionary, perlocutionary and illocutionary acts, which form the basis of speech units, in the process of communication is explained by analyzing examples of dialogic speech in English and Uzbek. It is explained at what point in the speech situation the above-mentioned acts are manifested and what role the speaker’s internal purpose in communication plays in this. At the same time, it is determined that in the performative formula, that is, in the process of openly expressing the speaker’s intention, tone, word order and inflection are the main means of expression. In terms of the structural structure of speech units and the communicative meaning they express, speech acts are divided into two groups: mediated and unmediated, and compared using examples. The article also analyzes the dialogue in terms of form and provides information about its main parts, replicas. It is determined that replicas are divided into stimulus and response parts, and the linguistic units used in them are different.